What Psychological Theories of Behavior Change Can Teach Us about Improving Hand Hygiene Adherence: Do We Mean What We Say?. (4th October 2017) - Corace, Kimberly; Smith, Jeffrey; MacDonald, Tara; Fabrigar, Leandre; Saedi, Arezou; Quirk, Jacquelyn; MacFarlane, Sam; Valickis, Debbie; Garber, Gary
Abstract: Background: Health care worker (HCW) hand hygiene is effective in reducing healthcare associated infections, yet hand hygiene rates are suboptimal. Psychological theories of behavior change can be used to improve and sustain hand hygiene adherence. While past research has examined HCW explicit attitudes towards hand hygiene (ie., self-reported attitudes), it is unclear if these explicit attitudes are consistent with implicit attitudes (ie., attitudes outside of one's awareness). Understanding HCW explicit and implicit attitudes is important when designing effective interventions to improve hand hygiene rates. This study examined explicit attitudes towards HCW hand hygiene and compared these to implicit attitudes. Methods: HCWs ( N = 420) from 70 long-term care facilities in Ontario, Canada completed: (1) a survey tool based on psychological theories of behavior change to examine explicit attitudes towards hand hygiene, and (2) a computer administered implicit association test (IAT) and affect misattribution procedure (AMP) to evaluate implicit attitudes towards hand hygiene. Sociodemographics and self-reported hand hygiene adherence were measured. Factor analysis was performed to identify themes. Correlations were conducted between explicit and implicit measures. Results: Factor analysis identified key explicit attitudes themes: (1) beliefs about consequences to self and others, (2) environmental resources, (3) time pressure and workload, and (4) social/professional role and identity. AMP and IAT results indicated that these procedures can be successfully applied to hand hygiene. While results suggested implicit positive attitudes towards hand hygiene, implicit test scores were neither correlated with explicit attitudes nor with self-reported hand hygiene adherence. Conclusion: Explicit attitudes did not predict implicit attitudes. So, what we say is not always what we really think or do. Interventions have successfully targeted implicit attitudes to foster behavior change when targeting explicit attitudes alone did not work. This is yet to be explored in the hand hygiene arena, and is a key area for future research in order to guide the development of successful interventions to sustainably improve hand hygiene rates. Disclosures: All authors: No reported disclosures.